The increase in turnover of steel-teeming ladles with a combined lining at the steelmaking production in OJSC «BSW – Management Company of Holding «BMC» - A. L. Artamoshin; A. K. Turygin; D. N. Khvesenya (Литьë и металлургия, 2019)
Currently, there is a need to increase the turnover of steel-teeming ladles ESPC-1,2, in connection with which the actual question was to reduce the duration of preparation of steel ladles to work. On steel ladles with a combined lining, one of the solution to this problem is to reduce the duration of drying and heating of the concrete working lining, but there is a risk of «undermining» the concrete mass due to the rapid warming of temperature. During the tests of the concrete mass from the manufacturer «A» for the period 2016–2018 the duration of drying and heating was reduced from 52 to 37 hours. Average overhaul life and durability of the concrete lining has increased by 37% and amounted to 96 meltings.